Defending Against Cyber-Attacks on the Internet of Things - Abdalrahman, Ghazi Abdalla; Varol, Hacer (Ieee, 2019)
IoT is a network of machines that communicate with each other, making smart decisions that help people and corporations to take control of their ventures. In recent years, the prevalence of IoT devices has increased dramatically, a phenomenon that has made users more vulnerable to cyber-attacks. As IoT becomes a staple of modern life, it is now essential to take cyber security seriously if cyber-attacks are to be prevented. It is therefore necessary to enhance the security of connected devices. One of the ways in which this can be achieved is through developing a deeper understanding of the attack types and motivations. Attacks are often traced to a weak link in the security network, meaning that connected devices serve as the chief target for cyber-attackers. Hackers are active in detecting these weak links to take control of these devices' advantages. IoT faces many challenges, but it is the enormous challenges to security that should be considered the most pressing.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: IoT; Cyber-attacks; M2M; Cyber-Security